(untitled) (Global Journal of Science Frontier Research, 2012)
This study was aimed at identifying the ecotype Apis mellifera subspecies in the savannah vegetation zone of Nigeria based on wing morphology and landmarks variations of samples collected from five States of savannah agroecological zone in the country. The measured variables were subjected to analysis with parametric statistic tools of mean, standard deviation and standard error. The distribution and relation between them were subjected to two step cluster analysis. Morphoclusters means were presented in centroids and also the simultaneous confidence intervals (95%) of means values of wing morphometric and landmarks were expressed. Savannah vegetation honeybee samples were classified into two distinct morphoclusters. Morphoclusters 1 constituted 56.4% of honeybees in the region while morphoclusters 2 had 43.6%. The within cluster percentage of state of honeybee showed all honeybee samples collected from Kebbi (100%) State were of morphoclusters 1 and also, morphoclusters 2 in Kaduna (100%) and Kwara (100%)States.